Extent and control standards of grouting reinforcement for underwater karst shield tunnels - Xu, Peng; Song, Xiangshuai; Cao, Lei; Sun, Heng (Frontiers in Earth Science, 2025)
In urban regions with karst developments, grouting is commonly utilized to fill cavities. However, the extent and control standards of grouting reinforcement are primarily determined through experience and field testing, which poses challenges in ensuring its effectiveness. Based on the instability mechanism of surrounding rocks in underwater karst shield tunnels, this study develops a mechanical model for analyzing the grouting reinforcement extent of such tunnels using strength theory. The reinforcement range for karst formations at various tunnel locations is clarified, and corresponding grouting reinforcement control standards are proposed based on cusp catastrophe theory. The findings indicate the following: the primary cause of surrounding rock instability in underwater karst shield tunnels is that the reduction in surrounding rock thickness during shield tunneling modifies the original constraints and boundary conditions and disrupts the initial equilibrium state. These changes influence the water content of the surrounding rocks and disturb the surrounding rock and soil mass, leading to surrounding rock instability. When grouting causes damage to the surrounding rocks between the karst and tunnel, the system is simplified into cantilever beam and plate models for analysis. It is determined that the grouting reinforcement extent is primarily influenced by factors such as karst size, properties of the karst filling material, and tunnel span. The total potential energy of the rock mass between the karst and tunnel is calculated, leading to the development of an instability and catastrophe model for the surrounding rocks. The proposed grouting reinforcement control standards are mainly dependent on factors such as the distance of the karst, characteristics of the reinforced surrounding rocks, shield machine support force, material properties post-reinforcement, and karst size.